Dukungan Sosial dan Lingkungan Sekolah terhadap Kesejahteraan Psikologis Siswa SMA - Suhariningsih, Utami (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2025)
The psychological well-being of high school students is a crucial factor in supporting academic success and socio-emotional development. However, this well-being is not solely influenced by internal factors, but also significantly shaped by social support from family, teachers, and peers, as well as the quality of the school environment. This article aims to comprehensively examine the relationship between social support and the school environment in relation to high school students' psychological well-being through a literature review approach. The method employed is a systematic review of 19 relevant national and international scholarly sources, including quantitative and qualitative studies as well as theoretical reviews. Data sources were retrieved from online academic journal databases, selected based on recency, relevance, and contribution to the development of adolescent psychological well-being studies. Findings indicate that social support serves as a protective factor that enhances students' resilience, sense of belonging, and life satisfaction. A positive school environment—characterized by a conducive learning climate, healthy interpersonal relationships, and anti-bullying policies—has been shown to support mental health and increase student engagement in learning processes. The integration of social support and a positive school environment creates a complementary ecosystem that fosters optimal psychological well-being among students. Conversely, a lack of synergy between these factors increases the risk of psychological issues. This article underscores the importance of a holistic and collaborative approach in promoting the psychological well-being of high school students, emphasizing the synergy between families, schools, and the broader community. Practical implications include the need for education policies that prioritize mental health, teacher training, and sustainable school-based interventions.